Oral and Lower Extremity Ulcers as the Initial Presentation of Granulomatosis with Polyangiitis - Mohammed Omar Al Salihi; Bianca Dominguez; Viresh Mohanlal; S. J. Carlan (Case Reports in Medicine)
Background. Granulomatosis with polyangiitis (GPA) is a small vessel vasculitis characterized by lung and kidney involvement. It is typically a disease of white females and has a poor prognosis with the average life expectancy of 5 months for a patient without treatment. Oral and skin ulcers are considered to be rare presentations. Case. A 39-year-old black male presented to the hospital with oral and skin ulcers and was diagnosed with GPA based on the biopsies of both cutaneous lesions and kidney. He was started on rituximab with minimal improvement. Later he was admitted to the ICU and had plasmapheresis, and he gradually improved and was discharged home 8 days after admission. Conclusion. GPA is an aggressive vascular disorder resulting in possible organ system damage and failure. The role of the sickle cell trait in this patient is undefined, but this combination of gender, race, and presenting symptoms in GPA is extremely unusual.